2014
DOI: 10.1016/j.ajog.2014.03.066
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fibroid characteristics on pregnancy outcome

Abstract: Objective: To assess the influence of different characteristics of fibroids on pregnancy outcome.Study design: We identified women with fibroids ≥4 cm in size on ultrasonography at the dating scan between January 2002 and December 2012. The size (4-7cm, 7-10cm, >10cm), number (multiple/single), location (lower uterus/body of uterus) and type (intramural, combination of intramural/subserosal, subserosal) were ascertained. Medical records were reviewed to obtain pregnancy outcomes (preterm delivery, birth weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 16 publications
3
46
2
3
Order By: Relevance
“…Symptoms manifest in 15%-30% of cases (3). This incapacitating pathology is responsible for complications, such as menometrorrhagia, leading to anemia, pelvic pain, and miscarriage, depending on the number, volume, and localization of myomas in the uterus (4). They constitute the first indication for hysterectomy (5).…”
mentioning
confidence: 98%
“…Symptoms manifest in 15%-30% of cases (3). This incapacitating pathology is responsible for complications, such as menometrorrhagia, leading to anemia, pelvic pain, and miscarriage, depending on the number, volume, and localization of myomas in the uterus (4). They constitute the first indication for hysterectomy (5).…”
mentioning
confidence: 98%
“…Our findings are consistent with previous reports that suggest the presence of fibroids, large fibroids in particular, places women at a higher risk for Cesarean delivery and increased blood loss at delivery. 1,[3][4][5]7,10,11 The relationship we found between presence of large fibroids and higher blood loss was preserved after adjusting for BMI and mode of delivery. However, there was no significant difference in blood transfusions between fibroid and nonfibroid groups, and therefore, does not appear to be a large adverse clinical effect as these women are not necessarily requiring transfusions more frequently.…”
Section: Commentmentioning
confidence: 69%
“…However, due to the relatively small sample size, we were not able to perform analysis by other characteristics of UFs. In two previous retrospective studies, preterm delivery was more common in multiple fibroids [23,24]. And in one study, fibroids in the lower part of uterus showed higher cesarean section rate, postpartum hemorrhage, greater estimated blood loss, and higher rates of admission for fibroid related pain [23].…”
Section: Discussionmentioning
confidence: 92%